3D Bioprinting of shear-thinning hybrid bioinks with excellent bioactivity derived from gellan/alginate and thixotropic magnesium phosphate-based gels. Issue 25 (2nd June 2020) - Chen, You; Xiong, Xiong; Liu, Xin; Cui, Rongwei; Wang, Chen; Zhao, Guoru; Zhi, Wei; Lu, Mengjie; Duan, Ke; Weng, Jie; Qu, Shuxin; Ge, Jianhua
Abstract : A novel shear-thinning hybrid bioink with good printability, mechanical support, biocompatibility, and bioactivity was developed by combining gellan gum, sodium alginate, and thixotropic magnesium phosphate-based gel (GG–SA/TMP-BG). Abstract : 3D Bioprinting is expected to become a strong tool for regenerative medicine, but satisfactory bioinks for the printing of constructs containing living cells are lacking due to the rigorous requirement of high printability and biocompatibility, which are often contradictory. Here, we have reported the development of a novel hybrid bioink by combining rigid gellan gum (GG), flexible sodium alginate (SA), and a bioactive substance thixotropic magnesium phosphate-based gel (TMP-BG). The ratio of these components was first optimized to obtain satisfactory gelating, mechanical, rheological, and printing properties. The formulated hybrid GG–SA/TMP-BG bioink had a good printability due to the shear-thinning and its multiple cross-linking by Mg 2+ and Ca 2+ . The tunable mechanical performance of the hybrid bioink could simulate various extracellular matrices of the different tissues and support integrity of 3D printing constructs. Moreover, the hybrid bioink induced apatite deposition during immersion in simulated body fluids, and also promoted cell proliferation in vitro . MG-63 osteosarcoma cells were dispersed in the bioink and printed into 3D constructs. The cells exhibited good cell survival due to the shear-thinning property of the bioink and the ion concentration used for cross-linking. The proliferation rate of the cells also significantly exceeded those in non-printed samples. Confocal microscopy revealed a homogeneous distribution of cells in the printed constructs, and survival for more than 7 d. In vivo animal experiments showed that the hybrid bioink without cells could induce osteochondral repair. Therefore, this hybrid bioink has good printability, biocompatibility, mechanical support, and bioactivity, which is expected to have promising applications in 3D bioprinting.